Pharmacological Evaluation of Anti-hemorrhoidal activity in ethanolic leaf extract of Ageratum conyzoides L. - Nitisha Shah, Dr. Virender Kaur, Dr. Tirath Kumar (South Eastern European Journal of Public Health, 2025)
Objective- Millions of people throughout the world suffer from hemorrhoids, a common medical illness characterized by enlarged and irritated blood vessels in the rectal and anal regions. Modern medicine is still in its early stages of finding a definitive cure for hemorrhoids, as there is no established and clear-cut solution for this particular ailment. The purpose of this study was to examine the ethanolic leaf extract of Ageratum conyzoides L. (ELEAC) has any anti-hemorrhoidal properties in experimental animal models. Method- A. conyzoides ethanolic leaf extract was made, and its phytochemical screening was examined. Rats were separated into treatment groups after being given a standardized procedure to produce hemorrhoids. The effects of ELEAC on hemorrhoid size, rectal bleeding, and histological alterations in the anal area were assessed after it was given orally and topically. In addition, ano rectal coefficient, liver enzyme results were evaluated. Results- Flavonoids, alkaloids, and tannins were found in the ELEAC, according to the phytochemical examination. Treatment with the test extract dose-dependently decreased inflammation, rectal bleeding and hemorrhoid size, when compared to the control group, histopathological analysis of the anal area of treated rats revealed a reduction in congestion, edema, and vascular dilatation. Additionally, the extract exhibited antioxidant activity by reducing oxidative stress markers and anti-inflammatory activity. Conclusion- In experimental animal models, the ELEAC showed significant anti-hemorrhoidal action, presumably because of its antioxidant and anti-inflammatory characteristics. Additional research is required to understand the underlying processes and assess its therapeutic applicability in the treatment of hemorrhoids.